Real-world evaluation of safety and effectiveness of dydrogesterone in the management of threatened abortion - Nagarkatti, Rajendra; Mehra, Dolly; Mandal, Sudipa; Dhawan, Archana; Joshi, Priya; Nagarkatti, Nupur; Chinda, Monika; Jaiswal, Ashok (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Threatened abortion is a relatively common complication during pregnancy. Inadequate production of endogenous progesterone is implicated as a risk factor for miscarriages. Thus, supplementation of external progesterone can be used as a preventive strategy in these women. Dydrogesterone a stereoisomer of progesterone has a good safety and tolerability profile and is known to effectively prevent pregnancy loss in women with threatened miscarriage, however, real-world data safety and effectiveness analysis of dydrogesterone in Indian patients was lacking. Therefore, this real-world retrospective analysis of the case reports was done to evaluate the safety, effectiveness, compliance, and tolerability of oral dydrogesterone in the treatment of women with threatened abortion. Methods: Data was collected from 194 obstetricians and gynaecologists in India, on the use of oral dydrogesterone in women presenting with threatened abortion in the first trimester of pregnancy. Results: Completed case report forms of patients who met the eligibility criteria (n = 617) were considered for the analysis. The main presenting symptom was vaginal bleeding/spotting with an additional symptom of abdominal cramp/pelvic pain/low back pain in 364 (69.07%) patients. Miscarriage was reported in 45 (7.29%) patients and 23 (3.98%) patients needed surgical intervention before 20 weeks of gestation with dydrogesterone treatment. The median time for relief of symptoms from the start of dydrogesterone tablets was 3.32 days for low back pain, 3.9 days for abdominal pain, and 4.37 days for the establishment of hemostasis. Treatment with dydrogesterone was found to be well-tolerated and adverse events were reported in 3.72% of the patients. Conclusions: This retrospective analysis suggests that dydrogesterone is safe and effective in reducing the incidence of pregnancy loss in women with threatened abortion.